2020
DOI: 10.1101/2020.04.28.067363
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of a single-step, single-tube reverse transcription-loop-mediated isothermal amplification assay for rapid detection of SARS-CoV-2 RNA

Abstract: bioRxiv preprint 4 3 thermocycler capable of holding 65°C for 30 minutes and measure fluorescence in the FAM channel 4 4 at one-minute intervals. 4 5 Results: Assay evaluation by assessment of 157 clinical specimens previously screened by E-gene 4 6 RT-qPCR revealed assay sensitivity and specificity of 87% and 100%, respectively. Results were fast, 4 7 with an average time-to-positive (Tp) for 93 clinical samples of 14 minutes (SD +7 minutes). Using 4 8dilutions of SARS-CoV-2 virus spiked into UTM, we also eva… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
2
21
0
Order By: Relevance
“…RT-PCR remains the most sensitive nucleic acid amplification method for COVID-19 diagnosis compared to MCDA and LAMP. This result is in agreement with previous LAMP COVID-19 assays which showed RT-PCR having greater sensitivity 9-11 . The limit of detection for our MCDA N gene assay was 1000 copies/reaction or an equivalent N gene average Ct value of 32.4 (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…RT-PCR remains the most sensitive nucleic acid amplification method for COVID-19 diagnosis compared to MCDA and LAMP. This result is in agreement with previous LAMP COVID-19 assays which showed RT-PCR having greater sensitivity 9-11 . The limit of detection for our MCDA N gene assay was 1000 copies/reaction or an equivalent N gene average Ct value of 32.4 (Table 1).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the great advantage of having a rapid and accurate CLEIA is the ability for primary screening to establish a "gray zone" reserving definitive diagnosis by confirmatory NAAT testing. Reverse transcriptase loop-mediated isothermal amplification (LAMP) [7] has become the second most common NAAT after PCR with several advantages over PCR: rapid turn-around time within 30 minutes, ease of implementation, and potential utility at point of care using a simple device [6,9,[21][22][23][24][25]. We recently reported that LAMP had equivalent efficacy to PCR using saliva in both All rights reserved.…”
Section: Discussionmentioning
confidence: 99%
“…All SARS‐CoV‐2 infection cultures were conducted within the High Containment Facilities in a PC3 laboratory at the Doherty Institute. Stocks of SARS‐CoV‐2 isolate hCoV‐19/Australia/VIC01/2020 39 were produced as previously described 40 . To assess the potential for SARS‐CoV‐2 to infect and replicate virus genome, cells were pelleted by centrifugation, washed with PBS and pelleted again.…”
Section: Methodsmentioning
confidence: 99%
“…Stocks of SARS-CoV-2 isolate hCoV-19/ Australia/VIC01/2020 39 were produced as previously described. 40 To assess the potential for SARS-CoV-2 to infect and replicate virus genome, cells were pelleted by centrifugation, washed with PBS and pelleted again. The cells were then lysed and viral RNA extracted using the QiaAmp Viral RNA extraction kit (Qiagen, Australia) as per the manufacturer's instructions and stored at À80°C.…”
Section: Rna Extraction and Sars-cov2 Qrt-pcrmentioning
confidence: 99%